Prevalence of prehypertension and its associated factors among smokers attending Klinik Kesihatan Bandar Kota Bharu - Deris, Nor Khairi (2018)
Introduction : Cardiovascular diseases are the leading cause of premature death in our country. Among the risk factors for cardiovascular diseases are prehypertension and smoking. Up to date there was no study looking for associated factors for prehypertension among smokers. Objective : To determine the prevalence of prehypertension and its associated factors among smokers attending Klinik Kesihatan Bandar Kota Bharu. Methodology : A cross sectional study involving a total of 333 current smokers aged more than 18 years at Klinik Kesihatan Bandar Kota Bharu from January to April 2017 by using convenient sampling. Respondents answered a questionnaire consists of sociodemographic back ground, IPAQ-M, MyNCDs – dietary assessment and FTND-M and followed with physical measurements for BP,weight, height and waist circumference. Data was analysed using descriptive analysis and logistic regression. Result : The mean (SD) age of respondents was 32.6 (10.3) and 57.7% (192) of current smokers have prehypertension. Through multivariate analysis using multiple logistic regression test, this study showed age ( adjusted OR=1.03,95% CI 1.00, 1.05,p=0.020), BMI ( adjusted OR=1.1195% CI 1.03,1.20,p=0.006), family history of hypertension (adjusted OR=1,78,95% CI 1.04,2.71,p=0.034), unhealthy diet (adjusted OR= 4.48,95% CI 1.88,10.63,p=0.001) and central obesity (adjusted OR=2.68,95% CI 1.22,5.89,p=0.014) were the associated factors for prehypertension.Conclusion : Prehypertension is common among current smokers and associated with many factors. Lifestyle modifications need to be given to reduce the incidence of prehypertension and prevent from progressing to hypertension and cardiovascular disease.